Cross-cultural issues in local managers' education and training in foreign companies in the People's Republic of China: with specific reference to the Shanghai Economic Zone - Zhao, Li (2004)
The purpose of the research conducted is to investigate the effects of local managers' education and training on corporate culture in foreign companies in the People's Republic of China. In order to realise the purpose, the project sets up three corresponding aims. First, an examination of corporate values and the corresponding cross-cultural issues in Western companies in a Chinese context is given. Second, a prescription of various adaptation forms of these companies is provided. Finally, the effects of the training on the corporate culture are evaluated and presented. The study employs a qualitative methodology for the exploration. Foreign companies covering the main fields of business activities in China were selected with an emphasis on the two countries: the United Kingdom and the United States. Thirty participants from those sample companies were interviewed face-to-face with semi-structured questions. The fieldwork was carried out mainly in Shanghai, which is the biggest city and an economic zone in China. At the same time, documentation was used as a complementary method in terms of providing relevant information. Data were also collected from two Asian foreign enterprises in China for benchmark. Final results in light of the research purpose and aims indicate that a foreign company in China, which is internationally accepted, is likely to apply a corporate culture that accommodates both similarities and differences between the local culture and the original culture of the foreign parent company. Such a corporate culture is not judged by its form, for it is neither a typical culture of a Western organisation nor typical one of a Chinese enterprise. It allows the corporation to keep international standards and simultaneously be capable of cultivating local managers to accept it emotionally. In this sense, local managers' education and training need to be perceived as a cultural process and delivered in a flexible way. The effects of the training upon the corporate culture are identified.